AN INVESTIGATION OF THE STUDENTS’ SATISFACTION WITH THE ACADEMIC SERVICES GIVEN BY THE FACULTY OF TEACHER TRAINING AND EDUCATION, SRIWIJAYA UNIVERSITY - P. J. Hariswan (Sriwijaya University Learning and Education International Conference, 2018)
This study was aimed at finding out the students’ satisfaction with the academic services given by the Faculty of Teacher Training and Education, Faculty of Teacher Training and Education, Sriwijaya University in the aspects of Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The samples were the students of English Education Study Program in the third, fifth, and seventh semesters of Inderalaya Palembang campuses. The data were collected using questionnaires and documentation. The data were analyzed using simple statistic computation. The results of the analysis were then described. It was foumd that the students of English Education Study Program were satisfied with the academic services given by the Faculty of Teacher Training and Education, Sriwijaya University. The results showed that there was no student who fell into the UNSATISFACTORY category. 96% students were in SATISFIED category and only 4 % were in QUITE SATISFIED category. This group can also be categorised as SATISFIED. This finding shows that the students were satisfied with the academic services given by the Faculty of Teacher Training and Education, Sriwijaya University.